Blue Angels : A Portrait of Gold - Shul, Brian, 1948- (Mach 1, 1995)
Come fly with the world's most highly acclaimed and exciting flight demonstration team. For over 50 years, America's own Navy Blue Angels have inspired millions the world over with their aerial artistry. Now for the first time ever, here is a book that candidly explores the very essence of the Blue Angel experience